Start Writing: from sentence to paragraph (Graha Ilmu, 2015)
This book is writen for readers who want to learn how to write in English. Which is writing setences. Thus, this book is divided into two parts, Part I writing setence and part II writing paragraph. Part I is about the structure of paragraph, how to build coherence and unity of a paragraph and types paragraphs. This book provides excerises at the end of each unit which readers should do. Readers are suggested to provide ample time to do the excercises so that they will not only learn the theory but also to apply what they learn. Writing indeed is a skill that needs a lot of practice.